2016
DOI: 10.1038/cddiscovery.2015.67
|View full text |Cite|
|
Sign up to set email alerts
|

A Bowman–Birk inhibitor induces apoptosis in human breast adenocarcinoma through mitochondrial impairment and oxidative damage following proteasome 20S inhibition

Abstract: Proteasome inhibitors are emerging as a new class of chemopreventive agents and have gained huge importance as potential pharmacological tools in breast cancer treatment. Improved understanding of the role played by proteases and their specific inhibitors in humans offers novel and challenging opportunities for preventive and therapeutic intervention. In this study, we demonstrated that the Bowman–Birk protease inhibitor from Vigna unguiculata seeds, named black-eyed pea trypsin/chymotrypsin Inhibitor (BTCI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 63 publications
0
34
0
2
Order By: Relevance
“…Recently, Souza et al (2014) reported the effects of a BTCI on proteasome 20S in MCF-7 breast cancer cells and the catalytic activity of the purified 20S proteasome from horse erythrocytes, as well as the structural analysis of the BTCI-20S proteasome complex. Furthermore, Mehdad et al (2016) stated that BTCI significantly decreased human breast adenocarcinoma cell viability by inhibiting the activity of proteasome 20S, with an associated cytostatic effect at the G2/M phase of the cell cycle and an increase in apoptosis.…”
Section: Roles Of Plant Protease Inhibitors In Health and Disease Conmentioning
confidence: 99%
“…Recently, Souza et al (2014) reported the effects of a BTCI on proteasome 20S in MCF-7 breast cancer cells and the catalytic activity of the purified 20S proteasome from horse erythrocytes, as well as the structural analysis of the BTCI-20S proteasome complex. Furthermore, Mehdad et al (2016) stated that BTCI significantly decreased human breast adenocarcinoma cell viability by inhibiting the activity of proteasome 20S, with an associated cytostatic effect at the G2/M phase of the cell cycle and an increase in apoptosis.…”
Section: Roles Of Plant Protease Inhibitors In Health and Disease Conmentioning
confidence: 99%
“…It presents rich biotechnological potential as an anticarcinogenic agent, as a guanylin-enhancing natriuresis and renal functional response in rats, as a bradykinin-potentiating molecule, and as an insecticide, inhibiting the growth of larvae with agricultural importance [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BBI inhibits AGS gastric adenocarcinoma proliferation through the inhibition of VEGF, MMP‐2 and MMP‐9 production (Fereidunian et al ., ). Seed BBI induces apoptosis through intracellular reactive oxygen species‐induced mitochondrial damage following suppression of proteasome 20S activity in breast cancer cells (Mehdad et al ., ). In animal models, BBI also inhibits the growth of colon cancer in rats, prevents chemical‐carcinogen‐induced lung cancer in A/J mice, and prevents prostate neoplasms in rats and TRAP transgenic rats (Hernández‐Ledesma & Hsieh, ).…”
Section: The Chemopreventive Property Of Soy Proteins and Peptidesmentioning
confidence: 97%